The Selection of Thick Blades and Strength Analysis of Threaded Turbines Using Finite Element Methods - ATHOILLAH (nim : 13113024), AQIL
Energy is a very important thing in human life. One example of the energy most used by humans is electrical energy. However, the world's electricity supply has limits, requiring many power plants to help supply electricity to meet the daily needs of the world's citizens. There are various kinds of power plants in Indonesia, one of which uses hydropower. Aside from being a power plant, water flow is also used as irrigation that irrigates plantations and rice fields. Indonesia is an agricultural country which certainly has many irrigation channels. This irrigation channel is targeted to have two functions namely generating electricity and water to the rice fields. In this undergraduate task the authors choose the thickness of the turbine blades and the thickness of the welded joints on the screw turbine by first formulating the hydrostatic load into the operating load and reviewing the threadedness aspects of the screw turbine. Once the thickness is determined, a 3D model is created which will be simulated static strength with Ansys 16 Analisys Static Structural based on finite element method. The simulation results are validated by means of geometry validation, comparing simulation results and calculating a simple model, and calculating the axial forces reaction force of the turbine with error between theoretical and simulation of 0.31%. The results of this simulation and then performed a power analysis because it produces the voltage that occurs in the turbine. The results of the analysis indicate that the structure of this thread turbine is strong to withstand the work load that occurs. After that is done an analysis of whether the deformation that occurs does not exceed the limit of deformation is allowed. Finally selected a 3 mm thick blade, 3 mm welding thickness, and a thickness pipe of sch 20 (6.35 mm).